The factors that influencing entrepreneur choice of micro franchising as a business model in Malaysia - Asha Chandraseakaren; Nurul Nabilah Kholidin; Nurul Shuhaiza Amran; Nurul Umiraizani Shaiful Raizan (2016)
Franchise industry has been growing rapidly and it is being scope into a small business model that can afford by a new entrepreneur to join in franchise industry which called micro franchise. The main purpose of the study is to identify the relationship between the factors which are performance, training program, brand name, financial and risk towards the entrepreneurs’ choice of micro franchise and to determine the factors that most influencing the entrepreneurs’ choice of micro franchise. This study conducted in the scope of the micro franchisee all around Malaysia, with the object of the study is limited to the five independent variables which are performance, training program, brand name, financial and risk and the entrepreneurs’ decision making as the dependent variable. Samples are taken as much as the population which is all the 55 micro franchise that is registered under the Ministry of Domestic Trade, Cooperatives and Consumerism. The result of the study has shown that there is a significant relationship between training program, financial and risk while there is no significant relationship between performance and brand name. The researcher recommends using a combination of quantitative and qualitative approach for future researcher.